2018
DOI: 10.1016/j.ymthe.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Targeted Theranostic Delivery of miRs Arrests Abdominal Aortic Aneurysm Development

Abstract: Abdominal aortic aneurysm (AAA) is an often deadly disease without medical, non-invasive treatment options. The upregulation of vascular cell adhesion molecule-1 (VCAM-1) on aortic endothelium provides an early target epitope for a novel biotechnological theranostic approach. MicroRNA-126 was used as a therapeutic agent, based on its capability to downregulate VCAM-1 expression in endothelial cells and thereby reduces leukocyte adhesion and exerts anti-inflammatory effects. Ultrasound microbubbles were chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…23 In another study, microRNA mimics were coupled with microbubbles, which enable imaging as well as ultrasound-guided burst delivery, and an antibody against VCAM-1 to specifically target endothelial cells. 24 Thus, in the near future with an improved technique of cell-specific microRNA mimic delivery, cardiac-specific short-term overexpression of miR-212/132 could be used to prevent doxorubicin-induced cardiotoxicity. Another limitation of the AAV9 viral system that we used is that, despite higher cardiotropism, it also transduces other organs, and we cannot completely rule out effects mediated by transduction of other cell types or tissues.…”
Section: Discussionmentioning
confidence: 99%
“…23 In another study, microRNA mimics were coupled with microbubbles, which enable imaging as well as ultrasound-guided burst delivery, and an antibody against VCAM-1 to specifically target endothelial cells. 24 Thus, in the near future with an improved technique of cell-specific microRNA mimic delivery, cardiac-specific short-term overexpression of miR-212/132 could be used to prevent doxorubicin-induced cardiotoxicity. Another limitation of the AAV9 viral system that we used is that, despite higher cardiotropism, it also transduces other organs, and we cannot completely rule out effects mediated by transduction of other cell types or tissues.…”
Section: Discussionmentioning
confidence: 99%
“…MB-assisted imaging or targeted drug delivery can be achieved by bursting the MBs after their adhesion to the target wall. In this study, the effect of acoustic forces on the MB adhesion to the target wall was neglected due to their small impact on the MBs motion 7,67,68 . The current study addressed the SDM adhesion on the intended surface using the MBs ligands and AAA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In a novel preclinical study, a biotechnological theranostic approach was used in the AngII-ApoE -/- mouse model [ 92 ]. MicroRNA-126 was previously shown to downregulate vascular cell adhesion molecule-1 (VCAM-1) expression in endothelial cells and to exert anti-inflammatory effects by reduced leukocyte adhesion.…”
Section: Use Of New Imaging Methods To Study Aaa Rupturementioning
confidence: 99%
“…MicroRNA-126 was previously shown to downregulate vascular cell adhesion molecule-1 (VCAM-1) expression in endothelial cells and to exert anti-inflammatory effects by reduced leukocyte adhesion. The investigators used ultrasound-microbubbles coupled with VCAM-1-targeted antibodies (scFvmVCAM-1) and microRNA-126 mimic theranostic microbubbles (TargMB-M126) [ 92 ]. They showed that TargMB-M126 inhibited AngII-induced AAA.…”
Section: Use Of New Imaging Methods To Study Aaa Rupturementioning
confidence: 99%